Восточная экспедиция Вацлава Серошевского и Бронислава Пилсудского 1903 года = Vostochnaya ekspeditsiya Vatslava Seroshevskogo i Bronislava Pilsudskogo 1903 goda - БЕЛЯЕВА-САЧУК , Вероника (Historia i Świat, 2021)
The article presents the history of the Eastern Expedition of 1903, which was organized by the Imperial Russian Geographical Society. It was organized with the assistance of well-known Russian scientists and public figures. The purpose of the expedition was to conduct basic research in East Asia on the territory of north-eastern Manchuria (Dauria), in Japan, Korea and China. On the ground, the members of the expedition Sieroszewski and Piłsudski were actively supported by Russian officials and official representatives of the authorities. Due to the deterioration of Russian-Japanese relations, as well as the high cost of living in Hokkaido, the expedition ended in the autumn of 1903, having passed only two stages – research in Manchuria and Hokkaido. Three collections were collected during the expedition – on the culture of Barguts, Solons, Ainu and Japanese – which are kept in Kunstkamera.